Sustainability Reporting And Environmental Innovation In Enhancing Corporate Reputation: A Systematic Literature Review - Shinta Aini; Siti Mutmainah (Green Publisher Indonesia, 2025)
Climate change and stakeholder pressure have driven companies to adopt sustainability strategies, including sustainability reporting and environmental innovation. Both are considered effective in enhancing corporate reputation amid growing public awareness of social and environmental responsibility. This study aims to systematically review scholarly literature that discusses the influence of sustainability reporting and environmental innovation on corporate reputation. The method used is a Systematic Literature Review (SLR) with a descriptive qualitative approach, identifying 25 articles from leading scientific databases published between 2021 and 2025. The results show that both variables positively influence corporate reputation, whether examined separately or in an integrated manner. The integration of sustainability reporting with environmental innovation is perceived to build stronger public perception of a company's credibility and commitment to sustainability. Several factors, such as industry characteristics, regulatory pressure, organizational culture, and public perception, were found to moderate the strength of this influence. In conclusion, modern corporate reputation is largely shaped by how well a company combines transparency in reporting with tangible actions through continuous environmental innovation.